Structural heterogeneity and conformational relaxation in heme proteins - Chu, Kelvin (1995)
The influence of cooling rate upon the structural heterogeneity of sperm whale myoglobin solutions at cryogenic temperatures was studied. Sample cooling rates were varied by almost four orders of magnitude. FTIR spectra of the CO stretch frequency region reveal that the population of the A states is highly sensitive to the glass transition temperature T$\sb{\rm g}$ of the solvent, which is in turn sensitive to the cooling rate. The structural heterogeneity within each substate was assessed by temperature-derivative spectroscopy (TDS); no significant changes of barrier distributions were found. We conclude that cooling rate plays a negligible role in the structural heterogeneity of protein solutions, and that conformational substates are an intrinsic part of protein systems. Flash photolysis experiments using both O$\sb2$ and CO adducts of sperm whale and horse myoglobin reveal an intermediate process that separates geminate and solvent rebinding. This process, named process II, is caused by thermally-induced relaxation (TIR) of the protein from the photoproduct (Mb*) to the deoxy (Mb) configuration. The conformational change Mb* $→$ Mb was originally modelled as a smooth shift of the rebinding barrier distribution towards higher enthalpies by extrapolation of the spectral position of band III and rebinding enthalpy. Data from light-induced relaxation (LIR) experiments suggest that the relaxation proceeds in discrete steps. A four-well sequential model is proposed in which a conformational change separates the inner two wells. Made available in DSpace on 2011-05-07T13:24:56Z (GMT). No. of bitstreams: 2 license.txt: 4922 bytes, checksum: 910b249b4beec47e7ab768910c8f966f (MD5) 9624317.pdf: 2889408 bytes, checksum: 53450782f04bf0b4af76986041b3c1df (MD5) Previous issue date: 1995 Item marked as restricted to the 'UIUC Users [automated]' Group (id=2) by Howard Ding (hding2@illinois.edu) on 2011-05-07T14:54:28Z Item is restricted indefinitely. Restriction data tranferred 2014-07-01T11:25:19-05:00 ...